Recombinant PBP2a as a vaccine candidate against methicillin-resistant Staphylococcus aureus: Immunogenicity and protectivity. (July 2017) - Haghighat, Setareh; Siadat, Seyed Davar; Rezayat Sorkhabadi, Seyed Mehdi; Akhavan Sepahi, Abbas; Sadat, Seyed Mehdi; Yazdi, Mohammad Hossein; Mahdavi, Mehdi
Abstract: Methicillin-resistant Staphylococcus aureus infections are focal and development of an effective vaccine can help to control this infection. Here, recombinant PBP2a was studied in mouse model. Following the preparation of recombinant PBP2a, Balb/c mice were injected subcutaneously with 20 μg of r-PBP2a formulated in Freund's adjuvant three times with three weeks intervals with proper control group. Total and specific isotype antibodies were evaluated on sera by ELISA. Opsonophagocytic activity was also investigated on the sera samples. Intraperitonealchallenge with a sub-lethal dose of MRSA (5 × 10 8  CFU) was done in experimental mice. Following that, the number of bacteria from kidneys of experimental mice were determined. Survival rate was recorded for 60 days. Significant increase of antibody with high level of IgG1, IgG2a and IgG2b isotypes was demonstrated in vaccinated mice versus the control group (P < 0.005). The bacterial load in the kidneys from immunized mice was 1000 times less thancontrol group (PBS) and opsonophagocytic activity of immunized mice sera significantly increased (P < 0.0001). Finally the life span of immunized mice after bacterial challenge was extended versus control mice. These results may indicate the capacity of PBP2a as a candidate vaccine to control the MRSA infections. Highlights: Immunization with r-PBP2a induced specific antibodies capable of effectively eliminating bacteria in kidney. Immunization with r-PBP2a as a candidate vaccine increased protectivity in experimental challenge. PBP2a is a valuable target for the development of vaccine candidate against methicillin-resistant Staphylococcus aureus.